Amorphous Molecular Materials for Directed Supercontinuum Generation. Issue 12 (25th November 2021) - Dehnen, Stefanie; Schreiner, Peter R.; Chatterjee, Sangam; Volz, Kerstin; Rosemann, Nils W.; Pilgrim, Wolf‐Christian; Mollenhauer, Doreen; Sanna, Simone
Abstract: The front cover artwork is provided by Stefanie Dehnen, Kerstin Volz, Wolf‐Christian Pilgrim (Philipps University Marburg), Peter R. Schreiner, Sangam Chatterjee, Doreen Mollenhauer, Simone Sanna (Justus Liebig University Giessen), and Nils W. Rosemann (Karlsruhe Institute of Technology). The image illustrates the conversion of red light from a continuous wave (CW) infrared laser into directed white light when propagating through a sample of the inherently amorphous adamantane‐type cluster compound [(StySn)4 S6 ] (Sty=styryl). Cover design by Elisa Monte. Read the full text of the Minireview at 10.1002/cptc.202100130 . Abstract : "Amorphous molecular materials of the general type [(RT)4 E6 ] (R=organic group, T=group 14 atom, E=chalcogen atom), which are capable of converting infrared light from an inexpensive CW laser diode into highly directional white light are surveyed. This type of white‐light generation (WLG) was previously unknown, and the physical mechanism behind it still requires concise explanation. The necessary preconditions that a compound needs to fulfil for WLG are the following: (a) it needs to be amorphous (inherently or upon amorphization) and (b) it must contain electron‐rich, cyclic organic ligands R…" This and more about the story behind the front cover can be found in the Minireview at 10.1002/cptc.202100130 .